The Role of Teachers in Improving Student Learning Outcomes in Thematic Learning through the Use of The Environment As a Learning Resource - Ahmad Zaki; Suparno Suparno; Lukman Nulhakim (Universitas Pendidikan Ganesha, 2021)
The low student learning outcomes are caused because, in the learning process, the teacher dominantly delivers the material. There are still many students having difficulty understanding the subject matter. The purpose of this study was to analyze the process of implementing thematic learning using the environment as a learning resource during the Covid 19 pandemic and to analyze the results of implementing thematic learning through the use of the environment as a learning resource during the Covid 19 pandemic. This type of research is qualitative research with a qualitative approach. The research subjects were third-grade elementary school students. The object of research is the role of the teacher in improving learning outcomes. Techniques to collect data through observation studies, interviews, and documentation. Data analysis was carried out in three stages: data reduction, data presentation, and conclusion/verification. This research shows that in this pandemic condition, learning activities are very disturbed, so that students are limited in carrying out learning activities. Using the environment as a learning resource can attract students' attention to be motivated to learn.